MANAJEMEN KINERJA GURU TERHADAP EFISIENSI BELAJAR SISWA: IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN - Putri, Intan Zulfa Atarria; Oktavia, Lailil; Abakar, Ali Abakar Ben; Trihantoyo, Syunu; Sholeh, Muhamad (Jurnal Manajemen Pendidikan, 2025)
Human resource management in educational settings plays a vital role in improving the quality of teaching and learning effectiveness. This study highlights aspects such as workforce planning, recruitment, training, performance evaluation, and incentives for teachers to enhance their motivation and performance. The results show that teacher development strategies, including technology-based training and professional development programs, contribute significantly to improving student learning efficiency. Teachers who receive ongoing training are better able to implement innovative teaching methods, improve classroom interactions, and create a more effective learning environment. In addition, teacher well-being, both in terms of incentives and psychological support, plays a role in increasing job satisfaction which has a direct impact on teaching performance. This study recommends a more strategic and technology-based approach to human resource management to improve the overall quality of education.